Family Psychoeducation in Reducing the Occurrence of Depression in Elderly: A Systematic Review - Cece Indriani; Yati Sri Hayati; Titin Andri Wihastuti (GoAcademica Research & Publishing, 2020)
Depression is a chronic prevalence and recurrence disturbance. Depression in the elderly characterized by sadness, low interested in doing activity, and inability to feel happiness. But most families ignore it because they think it is a common problem in the elderly. Family psychoeducation therapy is one of the elements of family mental health care programs by providing information, education through therapeutic communication to reduce the scale of depression in the elderly. This systematic review aimed to determine family psychoeducation in reducing the occurrence of depression in the elderly.This systematic review begins with a question in advance and specify the destination, then search for the exact keyword searching to identify the data required in accordance with the purpose of the method of